Diego J. Liñán Nogueras y Pablo J. Martín Rodríguez (dirs.): Estado de Derecho y Unión Europea, Tecnos, Madrid, 2018, 472 págs. - Di Comite, Valeria (Revista de Derecho Comunitario Europeo, 2019)
Sin resumen